Status of maternal health in Nepal - Vaidya, Achala (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3126/njog.v2i1.1466 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 1 - 3 May -June 2007